"Heal the World": A field experiment on the effects of music with prosocial lyrics on prosocial behavior. (March 2017) - Ruth, Nicolas
A significant amount of existing research has dealt with the negative effects of music on people's behavior, but only a few studies have shown that music with prosocial lyrics can increase prosocial behavior. This study focuses on the positive effects of music with prosocial lyrics on people in an everyday setting. Based on the general learning model, a field experiment ( N = 256, 66% female) was conducted to test whether people exposed to music with prosocial lyrics engaged in more prosocial behavior by buying more fair trade products compared to regular products than did those exposed to songs with neutral lyrics. Guests of a café were randomly assigned to either the prosocial or the neutral music condition and were monitored by two observers who were instructed to report the prosocial purchase (of fair trade coffee) and tipping behavior of the guests. The results indicated that there is a significant positive association between prosocial behavior and the prosocial lyrics of the songs played. The study shows that it is most likely that music with prosocial lyrics can influence one's prosocial purchase behavior in an everyday situation. The underlying mechanisms are still poorly researched, but these findings support the theoretical assumptions.